Polarization-insensitive and wide-angle metasurface to harvest dual-band energy in an ISM band. (16th February 2023) - Huang, Runze; Liu, Beijia; Liu, Xinyu; Lan, Shengchang; Wang, Nannan; Qiu, Jinghui
Abstract: This paper reports a novel dual-band metasurface structure to harvest electromagnetic energy in the environment efficiently. The unit structure comprises a novel Jerusalem cross on F4B substrate, a centrosymmetric structure which exhibits excellent stability under different polarization and incident angles of ISM bands (2.45 GHz and 5.8 GHz). Then the composite structure is designed to complete the array design of the metasurface. The harvetsed energy is guided to the back of the array through vias and collected by a dual-band differential input power combiner. Numerical simulation validates the dual-band, polarization-insensitive and wide-angle energy harvesting of the metasurface array constructed by the composite structure. The experimental results demonstrate that the metasurface array can achieve a peak energy harvesting efficiency of 91.6% and 94.9% under TE and TM polarization, respectively.